PENERAPAN MODEL PEMBELAJARAN PEER LED GUIDED INQUIRY (PLGI) UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN LARUTAN PENYANGGA DI KELAS XI MIA SMAN 1 PEKANBARU - Roza Maiyarni; R. Usman Rery; Susilawati Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purposes of research are to know the improvement of student learning achievement and value of influence by implementing Peer Led Guided Inquiry (PLGI) learning model on the buffers subject in the class XI MIA SMAN 1 Pekanbaru. This research is experimental research using Design Randomized Control Group Pretest-Posttest. The research sample consisted two class, class XI MIA 2 as experiment class and class XI MIA 3 as control class that has tested by normality test using Liliefors test and homogeneity test using equality of two average test. Hypothesis was done by using test-t right side. Research result shown that the implementation of PLGI learning model can improve student learning achievement on the buffers subject where tarithmetic = 3,33 > ttable = 1,67 with value of its influence to student learning achievement is 16,53%.Keywords : Learning Model Peer Led Guided Inquiry (PLGI), Learning Achievement, Buffers